Augmented Reality for teaching science: Students’ problem solving skill, motivation, and learning outcomes - Fitriana Nur Astuti; S. Suranto; Mohammad Masykuri (University of Muhammadiyah Malang, 2019)
Besides learning outcomes, motivation and problem solving skill are the essential indicators for successful learning. Hence, the existence of learning media which considerably follow the advance of technology has been assumed to be able to support the achievement of the indicators mentioned. Thus, the current research aimed at implementing the Augmented Reality (AR) technology to improve students’ problem solving skill, motivation, and learning outcomes. The sample was 56 of eighth graders which covered the both control and experimental classes. This quasi experimental research employed test and observation sheet as the instruments. The data was analyzed using one-way analysis of covariance (ANCOVA). The ANCOVA test results showed that were significance differences of the three indicators (problem solving skills, motivation, and learning outcomes) achieved, in which the experimental class was higher than control class. In conclusion, the AR can influence students’ problem solving skills, motivation, and learning outcomes.